Scheduler simulation using iSPD, an iconic-based computer grid simulator - Menezes, Denison [UNESP]; Manacero, Aleardo [UNESP]; Lobato, Renata Spolon [UNESP]; Da Silva, Diogo T. [UNESP]; Lobato, Renata Spolon [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Increased accessibility to high-performance computing resources has created a demand for user support through performance evaluation tools like the iSPD (iconic Simulator for Parallel and Distributed systems), a simulator based on iconic modelling for distributed environments such as computer grids. It was developed to make it easier for general users to create their grid models, including allocation and scheduling algorithms. This paper describes how schedulers are managed by iSPD and how users can easily adopt the scheduling policy that improves the system being simulated. A thorough description of iSPD is given, detailing its scheduler manager. Some comparisons between iSPD and Simgrid simulations, including runs of the simulated environment in a real cluster, are also presented. © 2012 IEEE.
Keywords: grid computing; grid simulation; scheduling policy; Computer grid; Distributed environments; Grid model; Grid simulations; High-performance computing resources; Parallel and distributed systems; Performance evaluation; Scheduling policies; Simulated environment; User support; Computer software selection and evaluation; Computer systems; Managers; Scheduling; Scheduling algorithms; Simulators; Grid computing